2018
DOI: 10.1021/acs.jafc.8b02844
|View full text |Cite
|
Sign up to set email alerts
|

Protein Oxidation in Plant Protein-Based Fibrous Products: Effects of Encapsulated Iron and Process Conditions

Abstract: Plant protein-based fibrous structures have recently attracted attention because of their potential as meat replacer formulations. It is, however, unclear how the process conditions and fortification with micronutrients may affect the chemical stability of such products. Therefore, we aimed to investigate the effects of process conditions and the incorporation of iron (free and encapsulated) on protein oxidation in a soy protein-based fibrous product. First, the physicochemical stability of iron-loaded pea pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 30 publications
4
38
0
Order By: Relevance
“…Overall, we see that a heat- and shear-based process can promote soy protein oxidation, which is in line with previous research. 18…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, we see that a heat- and shear-based process can promote soy protein oxidation, which is in line with previous research. 18…”
Section: Resultsmentioning
confidence: 99%
“…The separation of protein fractions from processed protein-based matrices to measure the protein-bound carbonyl content and the 2,4-dinitrophenylhydrazine (DNPH) method were done according to Soglia et al, 19 with minor modifications as described previously. 18…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since oxidized proteins are involved in the onset and severity of diverse diseases, the hypothesis that the intake of oxidized proteins may contribute to in vivo oxidative stress and certain pathological conditions seems reasonable. This hypothesis is furthermore supported by the growing concern about the impact of animal‐source proteins on human health, given that such proteins are particularly susceptible to oxidation (Estevez, Ollilainen, & Heinonen, ; Estévez, ; Estrada et al., ). Interestingly, Youngman, Park, and Ames () have reported already 26 years ago that protein oxidation associated with aging is reduced by dietary restriction of proteins, which clearly emphasizes the connection between protein intake and in vivo protein oxidation.…”
Section: Introductionmentioning
confidence: 96%
“…And it is reasonable to hypothesize that the intake of oxidized proteins may be associated with certain pathological conditions and in vivo oxidative stress. This is supported by the growing concern about the impact of animal source proteins on human health, given that such proteins are particularly susceptible to oxidation (Estevez, 2015;Estradaetal et al, 2018). Studies have reported that aging related oxidation of protein is reduced by dietary protein restriction, which clearly emphasizes the link between protein intake and in vivo protein oxidation (Youngman et al, 1992).…”
Section: Introductionmentioning
confidence: 99%